Kitābu Al-‘Ain: Metode Penggunaan dan Pengaruhnya Dalam Perkembangan Kosakata Bahasa Arab - Prabowo Adi Widayat (Institut Agama Islam Negeri Metro, 2019)
The development of language in a group or community is influenced by the systematic changes in daily interaction and communication. Dictionaries become a documentation of language development through syntactic and morphological aspects and then recorded. Kitab al-‘ain written and compiled by Syaikh Khalil has provided a treasure of Arabic vocabulary which is certainly very useful for those who are observers of Arabic and studying it. The formation and alteration of Arabic vocabulary always begins with phonetic aspects which are then documented in the form of writings that are recorded. Therefore, the dictionary as the end result of the lecsycographic work is to gather all the vocabulary in a language and make the dictionary as the container of a set of vocabulary that has a cultural background that serves to accommodate the concepts of Culture of the speaking community. The morphological process of Arabic vocabulary in the dictionary aims to bind utterances which often are not maintained by the formation process so that with the emergence of an Arabic dictionary the order of language is good and correct will always be realized and maintained. Lexicology became the pioneer of the study in the lexicography. It is part of a language study that focuses the research of vocabulary and its meaning as well as its relevance with the dictionary drafting process.